Foreign Fighter Mobilization: YPG Volunteers in Their Own Words - Malet, David (Terrorism and political violence, 2025)
This article presents data from interviews with eighteen individuals from Western countries who volunteered to fight in Syria with the Kurdish YPG against the Islamic State. We find that, despite predictions in the literature about ideological or religious indoctrination as the primary factor motivating foreign fighter mobilization, respondents described their decisions to join YPG determined by two individual-level factors: The first was precipitating new information, such as viewing war crimes videos, which was an emotional tipping point for volunteers already interested in the conflict. The second factor was the preconditions, or permissive conditions, that permitted them to leave their home countries, such as the end of a lease. The data adds richness to models of militant activity by indicating that it may not be a linear transmissive process but one that is dependent on the alignment of variables specific to the subject.